Performance Evaluation of Stock Price Indexes in the Indonesia Stock Exchange - Robiyanto, Robiyanto (International Research Journal of Business Studies, 2017)
This study evaluates the performance of stock price indexes in the Indonesia Stock Exchange by using Sharpe Index, Treynor Ratio,Jensen Alpha, Adjusted Sharpe Index, Adjusted Jensen Index and Sortino Ratio. The stock price indexes evaluated are the Jakarta Composite Index (JCI), Sectoral Index consisting of 10 sectoral stock price indexes, LQ45 Index, Jakarta Islamic Index (JII), Kompas100Index, BISNIS-27 Index, PEFINDO25 Index, SRI-KEHATI Index, Main Board Index (MBX), Developed Board Index (DBX). Data used in thisresearch is daily closing data of stock price indexes studied and riskfree interest rate represented by BI rate during period January 3, 2011, until July 17, 2017. Data were obtained from Bloomberg. The results of this study indicate that only three stock price indexes perform better than risk-free and stock-market instruments when calculated by using Sharpe Index, Treynor Ratio, Jensen Alpha, Adjusted Sharpe Index, and Adjusted Jensen Alpha Index. Meanwhile, when calculated by using the Sortino Ratio, the stock price index of miscellaneous industry sector has the best performance.